Implementing Corporate University Learning Methods to Accelerate the Foreign Language Competency of Indonesian Government Employees - Khoiriyah, Ira; Tamimi, Zahrina Zul (KnE Social Sciences, 2022)
Programs focusing on improving working practices during the pandemic, including competency development programs in higher education and government institutions, have been marked by a sense of urgency and creativity. This study explored the planned implementation of corporate university learning methods to help Indonesian government employees improve their foreign language skills. The research began with examining the training environment prior to the pandemic and how the pandemic altered the learning models. We wanted to know how the ASN Corporate University learning model influenced motivation to learn foreign languages. Secondly, we wanted to explore which learning experiences could help Indonesian State Civil Apparatus employees improve their foreign language skills. According to our review of the literature, systems likely will not return to their pre-pandemic state. As a result, future methods will need to include both substance-based and project-based approaches. The corporate university learning model best exemplifies the application of techniques focused on employees. As a result, the study only looked at a small portion of the competency development offered by the corporate university model: job-related competency development. Data were collected through an online survey of 126 State Civil Apparatus employees who worked for the Indonesian National Institute of Public Administration. Learning methods examined included giving a presentation in a foreign language, participating in international events, and fostering international cooperation. Across all methods, intrinsic motivation was found to be more prevalent than extrinsic motivation. Of all the methods tested, respondents were the most eager to participate in international events. These results should be considered in the design of future workplace foreign language learning. Keywords: corporate university, competency, development, motivation